Push and pull factors affecting in leaving academia - Kallio, Tomi; Siekkinen, Taru; Pekkola, Elias; Kivistö, Jussi; Nokkala, Terhi; Kuoppakangas, Päivikki (Springer, 2025)
This paper presents the findings of the push and pull factors that cause professionals to leave academia. Previous research has mostly focused on academic professionals' intent to leave their current organisations and largely neglected occupational turnover, that is, the cases where faculty abandon an academic career. The study included 40 semi-structured interviews and a national survey (N = 410) conducted in 2017. The interviewees consisted of three groups: previous faculty members who left academia, members of universities' upper management (deans, vice-rectors and HR managers) and upper managers and HR managers of public and private organisations employing previous academic faculty members. The survey was sent to all scholars who had left academia in Finland during 2010-2015. The qualitative empirical analysis suggests that most of the internal push factors that caused the academic professionals to leave were inversed external pull factors that lured them away from academia. However, it also hints that in many cases, certain individual factors seem to mediate the two. In practice this means that individual factors, such as lack of interest in research and/or teaching and unwillingness to compete in some positions, also contribute to the decision to leave academia.